Array - Nuriyah, Sinta (Paradigma, 2021)
This study intends to describe the symbolic interactionism of the phenomenon of "mabennya" akabhin, nambhei pajhu ", which means that the more frequent marriages are increasingly in demand because of the high number of divorces in Sumenep Regency, especially in Dungkek Village. The objectives of this study are 1) Identifying the objective conditions of marriage. 2) Identifying the function of marriage and divorce. 3) Identifying the views of the community on divorce and the position of the divorced person. 4) Assessing the meaning of divorce. The approach used in this research is qualitative. The theoretical basis used is George Herbert Mead’s theory of symbolic interactionism. The informants in this study were determined through purposive sampling technique. To collect data, the method used was Spradley ethnography with in-depth interviews, in accordance with the research objectives. The findings obtained from this study are: First, marriage is considered as a culture and part of the human life cycle which is the basis for the formation of a family formed on the basis of marital responsibility and the basic principles of marriage. Second, the function of marriage includes to get offspring, fulfill one’s desire, religion, foster a sense of responsibility and build a peaceful household. Meanwhile, the function of divorce is used as a medium for terminating the marriage relationship for various reasons that are legally acceptable. Third, society’s view of divorce is seen as a way to break up a husband and wife relationship for certain reasons in the hope that the child can still get the love that should be without any shortcomings or until a broken home. The status of people who are divorced, both in themselves, in their families and in society, can equally accept the status of widows or widowers because divorce has become a common practice. People conceptualize themselves as "I" and "Me" in accordance with the stimulus obtained to form a response in the form of an action consisting of symbols with various meanings of gestures and language. Fourth, marriage and divorce are likened to dating people who are "on and off" influenced by the old environment. It causes marriages to not last long, usually due to matchmaking, underage, inadequate preparation for household, psychological, problem pressures, third people, and lack of understanding, especially from Koran teachers and parents about the importance of marrying once according to religious norms and norms law. Keywords: Symbolic Interactionism, Divorce, In demand